Adolescents' views on discipline strategies of their mothers and fathers - Tan, Mary Jeselle Jane B.
This qualitative study aimed to identify the discipline strategies of mothers as perceived by adolescents, to identify the discipline strategies of fathers as perceived by adolescents, to compare the discipline strategies of mothers and fathers towards their adolescent children, and to determine the views of adolescents on their parents discipline strategies. This study is a qualitative research wherein responses of adolescents were categorized into themes. Thirty public high school students, 15 males and 15 females, who are aged 13 to 17 years and living with their parents,were interviewed by the researcher. Results revealed that adolescents experienced the same discipline strategies from their mothers and fathers. These discipline strategies were grouped into two: verbal and physical discipline. Under verbal discipline, discipline strategies were scolding and praising. However, under physical discipline, discipline strategies were inflicting physical pain, rewarding, and grounding. In terms of their views on these discipline strategies, adolescents responses were grouped into two: positive and negative views. For positive views, the themes for verbal discipline were teaching right and wrong, expression of love, motivation, parental right and fix to everything; and the themes for physical discipline were behavior deterrent, ineffective scolding, motivation, compliance, and parental right. On the other hand, for negative views, the themes for verbal discipline were emotionally damaging and violent tendency; and the themes for physical discipline were unnecessary, violent tendency, loss of freedom, and child abuse. After comparing the discipline strategies, this study revealed that most adolescents perceived their mothers as the ones who reprimand more than fathers. On the other hand, most of them perceived their fathers physical punishment as more painful than their mothers. This study recommends future researches to have respondents from different area to see if the study will yield to the same or different results when a different research locale with different culture is being considered.